Diabetes mellitus is associated with adverse structural and functional cardiac remodelling in chronic heart failure with reduced ejection fraction. (September 2016) - Walker, Andrew MN; Patel, Peysh A; Rajwani, Adil; Groves, David; Denby, Christine; Kearney, Lorraine; Sapsford, Robert J; Witte, Klaus K; Kearney, Mark T; Cubbon, Richard M
Background: Diabetes mellitus is associated with an increased risk of death and hospitalisation in patients with chronic heart failure. Better understanding of potential underlying mechanisms may aid the development of diabetes mellitus–specific chronic heart failure therapeutic strategies. Methods: Prospective observational cohort study of 628 patients with chronic heart failure associated with left ventricular systolic dysfunction receiving contemporary evidence-based therapy. Indices of cardiac structure and function, along with symptoms and biochemical parameters, were compared in patients with and without diabetes mellitus at study recruitment and 1 year later. Results: Patients with diabetes mellitus (24.2%) experienced higher rates of all-cause [hazard ratio, 2.3 (95% confidence interval, 1.8–3.0)] and chronic heart failure–specific mortality and hospitalisation despite comparable pharmacological and device-based therapies. At study recruitment, patients with diabetes mellitus were more symptomatic, required greater diuretic doses and more frequently had radiologic evidence of pulmonary oedema, despite higher left ventricular ejection fraction. They also exhibited echocardiographic evidence of increased left ventricular wall thickness and pulmonary arterial pressure. Diabetes mellitus was associated with reduced indices of heart rate variability and increased heart rate turbulence. During follow-up, patients with diabetes mellitus experienced less beneficial left ventricular remodelling and greater deterioration in renal function. Conclusion: Diabetes mellitus is associated with features of adverse structural and functional cardiac remodelling in patients with chronic heart failure.